FREEDOM OF SPEECH UNDER INTERNATIONAL LAW: MYANMAR'S ANTI-COUP DEMONSTRATION VIOLENCE CASE - Yordan Gunawan; Muhammad Nur Rifqi Amirullah; Vensky Ghaniiyyu Putri Permana; Mohammad Hazyar Arumbinang (JCH (Jurnal Cendekia Hukum), 2021)
The paper aims to examine the position of international law against violence committed by the Myanmar military known as Tatmadaw, against Myanmar which held anti-coup demonstrations in Myanmar. The research used the normative legal research method, with the main source of data collection of legal material containing normative law. The results showed that Myanmar is one of the countries in Southeast Asia whose government has been dominated by the military. In early 2021, the Tatmadaw staged a coup against Myanmar's President Aung San Suu Kyi. The tragedy began in the 2020 elections, in which the National Democratic League (NLD) was elected as the majority to sit in Myanmar's parliament. However, Tatmadaw could have no election results and no coup. Burmese, who did not support a coup by Myanmar's military, made a massive dip in the streets. Tatmadaw performs violent acts for action until 2019. However, from the direction of the protesters, some protesters became victims of violence by the Tatmadaw. It reflects the restrictions on the freedom of speech of the People of Myanmar. Free speech is an important right of the People of Myanmar to be part of the good Human Rights face-to-face by international law through arbitrary ministers by the Tatmadaw. The Tatmadaw's acts of violence against Myanmar violate human rights set forth in the Universal Declaration of Human Rights (UDHR) in articles 19 and 29. In addition, freedom of speech is also governed by the International Covenant on Civil and Political Rights in article 19.